Trichoepithelioma Arising in an Ovarian Mature Cystic Teratoma. (29th December 2016) - Suzuki, Takashi; Nakayama, Satoru; Muto, Haruka; Shimizu, Shinichi; Otsuki, Yoshiro; Adachi, Hiroshi; Murakoshi, Takeshi
Abstract : Here, we report an extremely rare case of trichoepithelioma (TE)—a benign epithelial tumor originating from the outer root sheath of a hair follicle—arising in an ovarian mature cystic teratoma (MCT) with fluorodeoxyglucose-positron emission tomography (FDG-PET) findings. A 48-year-old Japanese woman presented to our hospital for her annual follow-up of adenomyosis. Ultrasonography and magnetic resonance imaging revealed a left ovarian tumor with irregular-shaped septum, which was suspicious of malignancy. However, tumor marker levels were within normal range. On FDG-PET, the maximum standardized uptake value (SUVmax) of the tumor was 2.9. Laparotomy with left salpingooophorectomy was performed. Pathologic examination revealed the probability of TE, rather than basal cell carcinoma (BCC), arising in an ovarian MCT. After five years of follow-up, the patient had no sign of recurrence. The FDG-PET SUVmax was low in TE, as with other benign tumor. However, future investigation is needed to evaluate the findings of FDG-PET imaging in TE cases.